2021
DOI: 10.2147/ijgm.s329208
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of THBS1 is Related to Immunity and Chemotherapy Resistance in Gastric Cancer

Abstract: Purpose Thrombospondin 1 ( THBS1 ) is an endogenous inhibitor of angiogenesis, but it also promotes tumor invasion, metastasis, and immune response in the tumor environment. Previous research has found that THBS1 is highly expressed in many tumors and has a negative correlation with tumor prognosis. However, research on the relationship between THBS1 and immune infiltration in GC is less well documented, and the objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Based on our results, MSI was significantly related to EXTL3 expression in TCGA-PRAD, while TMB and TNB did not have significant associations with EXTL3 expression. To further seek EXTL3-related drugs in PCa, CellMiner database was utilized and this database was designed for facilitating the study and selection of anticancer drugs [ 45 , 46 ]. Our results showed that EXTL3 expression was negatively correlated with AFP464, AP-26113, dexrazoxane, LDK-378, palbociclib, having the potential to prevent the progress of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, MSI was significantly related to EXTL3 expression in TCGA-PRAD, while TMB and TNB did not have significant associations with EXTL3 expression. To further seek EXTL3-related drugs in PCa, CellMiner database was utilized and this database was designed for facilitating the study and selection of anticancer drugs [ 45 , 46 ]. Our results showed that EXTL3 expression was negatively correlated with AFP464, AP-26113, dexrazoxane, LDK-378, palbociclib, having the potential to prevent the progress of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of these proteins has been extensively implicated in a variety of malignancies’ progression and metastasis. ITGB1, FBN1, and THBS1 have not been coherently identified as putative “pan-cancer” early detection biomarkers because a similar study to this one has not been conducted previously [ 109 , 110 , 111 , 112 , 113 , 114 ]. Nonetheless, the notion of other pancancer biomarkers in prognostic detection has already been tested with promising results as highlighted in the DETECT-A clinical trial [ 115 , 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…THBS1 was the first member of the THBS to be identified and is thought to be an endogenous inhibitor of angiogenesis (Jeanne et al, 2015). Previous studies have shown that THBS1 is highly expressed in various tumors (Jayachandran et al, 2014;Pal et al, 2016;Kamijo et al, 2020;Zhang et al, 2021). Furthermore, Lidan et al have found that THBS1 was lowly expressed in AML patients, which may be induced by promoter methylation, and patients with low THBS1 expression had a shorter survival time; furthermore, Allogeneic Hematopoietic Stem Cell transplantation can overcome the adverse effects mediated by low THBS1 expression (Zhu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%